Students Mathematical Literacy through Ethnomathematics-based Learning - Suci Maulina; Junaidi Junaidi; Mahyatun Nufus; Nanda Rizka Maulida (Universitas Syiah Kuala, 2024)
Mathematical literacy is one of the 21st-century skills students need to have. However, the PISA 2022 results revealed that Indonesian students' mathematical literacy decreased. Therefore, the government suggests that teachers integrate literacy activities in the teaching and learning process, including mathematics learning. This study integrated ethnomathematics of Aceh culture as an attempt to develop students mathematical literacy. This study intends to describe students mathematical literacy through ethnomathematics-based learning in two school settings: suburban and rural. This study employed a descriptive method. The participants involved 42 Grade 10 students from suburban and rural high schools in Pidie Regency, Indonesia, selected by the purposive sampling technique. Data were collected from students' written answers to the problems listed in the worksheet and analyzed descriptively. The finding revealed that, overall, the mathematical literacy of suburban school students surpassed that of rural school students. Among the mathematical literacy aspects, employing received the highest score, and interpreting got the lowest for both schools. The implications of this study are discussed further in this paper.